Folkebibliotekets digitale tilbud under koronakrisen – en case studie fra Tromsø bibliotek og byarkiv - Skare, Roswitha (Nordic Journal of Library and Information Studies, 2021)
The Covid-19 pandemic caused a lockdown of public libraries’ buildings in Norway in March 2020 as was the case in almost every other European country. This article investigates the situation for the public library in Tromsø in the period from 12 March 2020 and towards a gradual reopening of the library building to the public in April the same year. The lockdown of the physical library building led to an increased use of digital resources, and the library continued its presence on social media platforms informing their users about those. The article focuses first on digital resources offered by the library before it investigates the libraries posting on Facebook during the first month of lockdown in Norway.